An experiment in forecasting with diabatic baroclinic model over India and neighbourhood (MAUSAM, 1975)
This paper contains the results of experiments in forecasting the flow patterns over India and neighbourhood at 850, 700, 500 and 300-mb levels with the help of a four-layer quasi-geostrophic diabatic model. The effects of the ground contour, latent heat of condensation and radiation have been taken into account for computation of the vertical velocity UJ. To bring out the salient features of the model in this paper, we present the results of a case study.